Evolution of Cybercrime Law in Legal Development in the Digital World - Ruddin, Isra; Subhan Zein SGN (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research explores the evolution of cybercrime law in the face of developments in information and communication technology (ICT) over the last few decades. The development of digital technology has provided countless benefits but has also given rise to increasingly complex threats in the form of cyber attacks and cybercrime. This research aims to investigate how cybercrime law has evolved in response to changes in ICT and how these developments have influenced the effectiveness of cybercrime law enforcement. This research also analyzes the role of cross-border cooperation in cybercrime law enforcement and how developments in international law have influenced countries' ability to deal with global cybercrime threats. The research results show that the evolution of cybercrime law includes the establishment of more specific cybercrime laws and stronger protection of personal data. Cross-border cooperation plays an important role in cybercrime law enforcement, including information exchange, joint prosecution, asset freezing, and extradition. Developments in international law, such as the Budapest Convention and the General Data Protection Regulation (GDPR), have provided the legal basis necessary for more effective cross-border cooperation. However, challenges remain, including legal and jurisdictional differences between countries that often hamper law enforcement efforts. Therefore, increasing international cooperation and efforts to overcome these obstacles is critical in maintaining security and privacy in the ever-evolving digital era